Strategi Pembelajaran Maharah Kitabah di Ma'had al-Jami'ah UIN Mataram - Faezal Hadi Putra; Baiq Ummi Kalsum; Haryati Haryati; Rifki Usmandi; Suparmanto Suparmanto (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2023)
Writing is a skill taught in learning Arabic. The learning aims to make students skilled in expressing ideas, Ideas and feelings in Arabic in writing. Writing skills training must always be directed towards the learning objectives with indicators of learning success, namely (1) being able to copy the sounds of words, phrases and sentences according to the language structure; (2) able to answer questions according to the reading text and sort them into good paragraphs; and (3) able to express ideas or compose both in a guided and free manner using vocabulary according to the specified theme. The third indicator is the attainment of the highest level of learning in Arabic Maharah Kitabah.